Korelasi Faktor-Faktor Produksi Agroforestri terhadap Pendapatan Petani Hutan Kemasyarakatan - Amiruddin, Amiruddin; Mudhofir, Muhammad Rifqi T (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
Agroforestry practices in Community Forests are considered to be one of the collaborative management strategies with communities around forest areas. Forest farmers, as the primary actors in HKm management, contribute to forest management and benefit economically from land use. Forest farmers' income can be affected by production parameters such as land area, plant number, and agricultural infrastructure. This study examines the correlation between various production parameters of agroforestry-based HKm management, particularly their impact on HKm farmers' income. The study was conducted in Central Lombok Regency and West Lombok Regency, West Nusa Tenggara Province. Results showed a positive relationship in almost all agroforestry production factors with HKm farmers' incomes. The significant correlation between the ownership of multi-purpose tree species (MPTS) and agroforestry plants, HKm land area, costs, and revenue of HKm farmers suggests that forest farmers engage in agroforestry activities on a large scale.